Adoption leave: time for an equal motherhood - Abeyrathna, A.H.M.D.L. (Faculty of Law, University of Colombo, 2021)
Motherhood is a unique experience for women whether it is attained through natural birth or by adoption. Adoption is a process where persons adopt children according to the legal framework, who are born to some other parents. After having an adoption order, the adopted child gets the exclusive position of a child born to the adopter in lawful wedlock, even though there are several discriminations faced by the adoptive mother, especially with regard to maternity leave as they are not entitled in Sri Lankan legal context. The main objective of this research is to analyze the need of introducing adoption leave in Sri Lanka to allow adoptive mother to bond with adopted child and to provide opportunity for the child to acclimatize to the new mother. For this purpose, the following aspects are addressed by this research; (i) similarities and differences between natural mothers and adoptive mothers; (ii) current legal position of adoptive mothers in Sri Lanka; and (iii) rationale behind providing adoptive leave. The study uses qualitative analysis in order to gain insights into the existing laws relating to maternity leave in Sri Lanka. The research also adopts a comparative study of existing statutes and literature mainly from the UK, and South Africa and the international documents such as ILO conventions, CEDAW, and UNCRC. The research showcases the adoption leave is equally important as maternity leave, especially when the adopted child is under a certain age. The restrictions and the guidelines to adhere when providing adoption leave are also identified based on the comparative analysis. In conclusion, the research provides a timely and necessary study of the need of introducing adoption leave to Sri Lanka in order to protect the rights of adoptive mothers with several restrictions and guidelines.
Keywords: adoption leave; adopted child; adoptive mother; natural child; maternity leave